Evaluasi User Experience pada Sistem Informasi Manajemen Masjid menggunakan Metode Usability Testing (Studi Kasus: Masjid Hidayatullah Kalasan) - Farizqi, Rafli Ahmad; Kholid Haryono (Universitas Pahlawan Tuanku Tambusai, 2024)
The study aims to evaluate the user experience of the Hidayatullah Kalasan Management Information System (SIMMAS) website with the aim of determining the relevance of existing features to the needs of other mosques. SIMMAS Hidayatullah is a platform that provides information about pilgrims' data around Hidayatullah Kalasan Mosque, including data such as pilgrims' citizen data, family cards, mukim, expertise, and worship. The results show that some features are not yet fully in line with the needs of other mosques. For example, users feel that blood type data is not really needed for data collection of mosque worshipers. In Usability Testing using the System Usability Scale, this website received a score of 77.5 which is equivalent to grade B, slightly above the minimum grade C score of 68, indicating that most users are satisfied with the experience of using this website, although there is still room for improvement.Keyword : Information System, User Experience, Usability Testing, System Usability Scale, Website